RESPON MASYARAKAT TERHADAP PROGRAM CORPORATE SOCIAL RESPONSIBILITY (CSR) PT. PERTAMINA RU II DUMAI - Theresa Laosi Retno Ningsih; Yoserizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Research on the public response to the Corporate Social Responsibility (CSR) program conducted by the author has the aim to find out how the public response to the research program about the public response to the Corporate Social Responsibility (CSR) program held by PT. Pertamina RU II Dumai and to find out what factors influence the response of the community. The location of the study was in Tanjung Palas and Jaya Mukti Sub-Districts where the people who received the Research program about the community response to the Corporate Social Responsibility (CSR) program were spread in two villages. The method used in the study was quantitative with descriptive analysis, the data collection technique used the survey method because the number of respondents was only 20 people and data collection was obtained through questionnaires and documentation. The results of the research in the field were discovered that the recipient community of the research program on the public response to the Corporate Social Responsibility (CSR) program as many as 17 people had known the program and the majority of the community had participated actively. The factors that influence people's response are knowledge, education, experience, and off-target factors. Communities that have education and experience tend to actively participate. The community also has grievances in areas that are less suitable for cultivating white oyster mushrooms and the lack of new members to continue the convection business. Community response to the research program on community response to the Corporate Social Responsibility (CSR) program has been good, this is evidenced by people's knowledge and community participation in participating in the programs held. The community contributes thoughts and suggestions.Keywords: Response, Program, Corporate Social Responsibility (CSR)